'I've Just Been Pretending I Can See This Stuff!': Group member voice in decision‐making with a hidden profile. (28th January 2021) - Nicholson, Dawn H.; Hopthrow, Tim; de Moura, Georgina Randsley; Travaglino, Giovanni A.
Abstract : This research seeks to expand our knowledge of what underlies group performance in Hidden Profile decision tasks, adopting a mixed methods approach. We created a new mental simulation intervention designed to improve group decision outcomes and information exchange and tested it across two studies. We supplemented our quantitative statistical analysis with Thematic Analysis, to explore and better understand the motivations and utterances of individual group members, which we contend are key to increasing understanding of the challenges operating at individual and group levels in Hidden Profile decision tasks. Much group decision‐making research uses quantitative methodologies, searching for causal explanations of why things happen as they do in group processes. As a subset of this area, existent Hidden Profile research is centred in the quantitative domain. Yet qualitative research can improve the understanding of group phenomena, such as communication style, which is important in groups' decision‐making. To our knowledge, no Hidden Profile research has taken a similar approach, so this paper makes a unique contribution. Results indicated the mental simulation had a positive effect on information exchange and decision quality in a Hidden Profile hiring task.